2016
DOI: 10.1021/acsami.6b08286
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nucleation of Diamond Films

Abstract: ABSTRACT:With the large differences in surface energy between film and substrate in combination with the low sticking coefficient of hydrocarbon radicals, nanocrystalline diamond growth on foreign substrates typically results in poor nucleation densities. A seeding technique is therefore required to realize pinhole-free and thin coalesced films. In this work, a chemical nucleation method for growth of diamond on nondiamond substrates based on 2,2-divinyladamantane is shown. After treating with the carbon-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It is interesting that nucleation of diamond from cage compounds of carbon and hydrogen atoms was also proposed for diamond growth by CVD technique from mixture of methane with hydrogen . Later the successful growth of CVD diamond crystals from adamantane seeds has been widely reported in the literature …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that nucleation of diamond from cage compounds of carbon and hydrogen atoms was also proposed for diamond growth by CVD technique from mixture of methane with hydrogen . Later the successful growth of CVD diamond crystals from adamantane seeds has been widely reported in the literature …”
Section: Introductionmentioning
confidence: 99%
“…[8] Later the successful growth of CVD diamond crystals from adamantane seeds has been widely reported in the literature. [9][10][11] High structural perfection and low impurity level are characteristic of HPHT nanodiamonds synthesized from hydrocarbons. So far, the mechanisms of diamonds synthesis from organics, as well as the luminescent properties of impurity centers formed in such diamonds were mainly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Such graphitic carbon is generally not seen in lms with high seeding density. 176 If we compare the diamond growth by Chen et al 174,175 with that of Tiwari et al 173 discussed above, a marginal increase in seeding density can be seen. However, this can be attributed to the solvent 177 even though in the case of Chen et al 174,175 they do not see in any noticeable enhancement in seeding due to the solvents.…”
Section: Chemical Nucleationmentioning
confidence: 86%
“…Recent research has shown that electrostatic adsorption and self-assembly on modified substrate surface results in very high nanocrysalline particle densities by taking advantage of the electrostatic interactions between the nanocrysalline particle and silicon surface. [17,18] In this study, the diamond nucleation on WC-Co was enhanced by considering the charge of the nanocrystalline diamond particles at varying pH-values.…”
Section: Introductionmentioning
confidence: 97%